PENGARUH PENDAPATAN ASLI DAERAH DAN JUMLAH PENDUDUK TERHADAP PRODUK DOMESTIK REGIONAL BRUTO (PDRB) KABUPATEN DAN KOTA DI PROVINSI ACEH - Maisarah Maisarah; Khairil Anwar (LPPM UNIMAL, 2023)
This study aims to analyze the effect of regional original income and population on the gross regional domestic product of districts and cities in Aceh province. The data used in this research is secondary data. This research model uses panel data regression. The results of the study partially show that regional own-source income has a positive and significant effect on the GRDP of districts and cities in Aceh province. Total population has a positive and significant effect on the GRDP of districts and cities in Aceh province. Local Own Revenue and Population have a positive and significant effect on the GRDP of Regencies and Cities in Aceh Province.